2022
DOI: 10.3390/ijms24010644
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Apoptosis: Current Challenges of Treatment and Drug Resistance in Multiple Myeloma

Abstract: Over the past two decades, the natural history of multiple myeloma (MM) has evolved dramatically, owing primarily to novel agents targeting MM in the bone marrow microenvironment (BMM) pathways. However, the mechanisms of resistance acquisition remain a mystery and are poorly understood. Autophagy and apoptosis are tightly controlled processes and play a critical role in the cell growth, development, and survival of MM. Genetic instability and abnormalities are two hallmarks of MM. During MM progression, plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 149 publications
0
13
0
Order By: Relevance
“…Apoptosis is a common mechanism of drug-induced tumor cell death, and altered apoptosis pathways are some of the important mechanisms underlying the development of the chemoresistance of cancer cells [36,37]. Studies have shown that apoptosis signaling pathways influence chemosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a common mechanism of drug-induced tumor cell death, and altered apoptosis pathways are some of the important mechanisms underlying the development of the chemoresistance of cancer cells [36,37]. Studies have shown that apoptosis signaling pathways influence chemosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to target both epigenetic and non-epigenetic factors highlights their promise in MM treatment, especially when used alongside other therapies [ 30 ]. Moreover, autophagy, an essential cellular mechanism responsible for the degradation and recycling of impaired organelles and proteins, assumes a multifaceted and ambivalent role in the pathology of MM [ 40 , 50 , 51 ]. This process facilitates cellular survival under conditions of stress by provisioning vital nutrients and energy, thereby contributing to the development of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM), the second most common blood cancer, is a plasma cell malignancy frequently accompanied by hypercalcemia, immune dysfunction, and renal failure [ [1] , [2] , [3] ]. Despite the employment of various therapeutic methods, such as immunomodulatory agents, proteasome inhibitors, and autologous stem cell transplantation (ASCT), MM remains an incurable disease with nearly 160,000 new cases and 106,000 deaths annually [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%